Galanin Receptor 2 Is Involved in Galanin-Induced Analgesic Effect by Activating PKC and CaMKII in the Nucleus Accumbens of Inflammatory Pain Rats - Li, Mengnan; Zhang, Xiaomin; Li, Chongyang; Liu, Yanan; Yang, Shuang; Xu, Shilian (Frontiers in Neuroscience, 2021)
It has been reported that galanin has an analgesic effect via activating galanin receptors (GALRs). This study focused on the involvement of GALR2 in the galanin-induced analgesic effect and its signaling mechanism in the nucleus accumbens (NAc) of inflammatory rats. Animal models were established through injecting carrageenan into the plantar of rats’ left hind paw. The results showed that GALR2 antagonist M871 weakened partially the galanin-induced increases in hind paw withdrawal latency (HWL) to thermal stimulation and hind paw withdrawal threshold (HWT) to mechanical stimulation in NAc of inflammatory rats. Moreover, the GALR2 agonist M1145 prolonged the HWL and HWT, while M871 blocked the M1145-induced increases in HWL and HWT. Western blotting showed that the phosphorylation of calcium/calmodulin-dependent protein kinase II (p-CaMKII) and protein kinase C (p-PKC) in NAc were upregulated after carrageenan injection, while p-PKC and p-CaMKII were downregulated after intra-NAc administration of M871. Furthermore, the CaMKII inhibitor KN93 and PKC inhibitor GO6983 attenuated M1145-induced increases in HWL and HWT in NAc of rats with inflammatory pain. These results prove that GALR2 is involved in the galanin-induced analgesic effect by activating CaMKII and PKC in NAc of inflammatory pain rats, implying that GALR2 agonists probably are potent therapeutic options for inflammatory pain.